The Basics of Cancer Immunotherapy (Springer International Publishing, 2018)
This book provides patients and their physicians (especially "non-oncologist" health care providers) with a clear and concise introduction to cancer immunotherapy, which, unlike traditional forms of cancer therapy, acts by boosting the patient's own immune system to fight cancer. The unique features of cancer immunotherapy make its management, monitoring and side-effects different from those of traditional cancer therapy. Especially novel are the side effects of cancer immunotherapy, necessitating greater awareness for both patients and physicians in order to minimize complications of therapy. The patient-friendly, concise, easy-to-understand, and up-to-date knowledge presented in this book will inform patients about the benefits and risks of cancer immunotherapy, and help them and their care providers to understand how immunotherapy would control their unique disease. Researchers and academic professionals in the field of cancer immunotherapy will also find clear and useful information to help them communicate with patients or address unresolved problems. Some key features of the book are: Expertise. All editors and authors are scientists and oncologists specializing in cancer immunotherapy, and are involved in scientific discovery from the early stage of immune-checkpoint inhibitors to today's daily patient care. Their insights, expertise and experience guarantee the high quality and authority in the science, medicine and practice of cancer immunotherapy. Patient-friendly. This book is written for cancer patients in order to meet their needs when considering immunotherapy. As an educational tool, this book will help the reader balance the risks and benefits based on both science and clinical facts, and therefore to make the best choice in receiving or withdrawing from immunotherapy. Disease Specificity. Cancer is a complicated disease involving multiple stages and pathology. Its response to immunotherapy is individualized and varies depending on cancer types. The authors' expertise in treating different types of cancers, including melanoma, lung, kidney, bladder, and lymphoma, provides disease-specific insights in applying immunotherapy to each disease.